2022
DOI: 10.1155/2022/7933166
|View full text |Cite|
|
Sign up to set email alerts
|

Study on the Influencing Mechanism of Human Chorionic Gonadotropin (hCG) on Oocyte Maturation in Patients with Polycystic Ovary Syndrome

Abstract: The study was aimed at investigating the influence of human chorionic gonadotropin (hCG) hormone on oocyte maturation in the patients with polycystic ovary syndrome (PCOS). A total of 54 patients with PCOS who received in vitro maturation (IVM) treatment in the Cheeloo College of Medicine, Shandong University, were divided into two groups: one group who underwent hCG injections was the observation group (OG; n = 27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%